MANAJEMEN STRATEGIK DALAM PENINGKATAN MUTU PENDIDIKAN DI MADRASAH ALIYAH NEGERI (MAN) 2 KOTA KANDAR LAMPUNG - Masrur, Muhammad; Anggraeni, Leni; Gusliana, Evi (JMPA (Jurnal Manajemen Pendidikan Al-Multazam), 2021)
This research is motivated by a phenomenon that says that education must be managed with strategic management in order to produce the most superior management to be developed. This research was conducted in Madrasah Aliyah Negeri (MAN) 2 Bandar Lampung City. The method used in this research is to use a qualitative approach with a multisite study. Data was collected through interviews, observation, and documentation. The results of this study conclude that: Strategic planning in Madrasah Aliyah Negeri (MAN) 2 Bandar Lampung City is carried out through activities, formation of a formulation team, formulation of vision and mission, analysis of opportunities, and threats, long-term plans, annual plans, improvement of learning, opening classes Bilingualism and improving the quality of educators. The strategic evaluation is carried out through official meetings, meetings with madrasa heads, committees, and waka, special meetings for madrasa heads and waka, meetings for teachers, employees, and madrasa heads, and committee meetings